Hubungan Dukungan Sosial Dengan Stres Akademik Pada Mahasiswa Penerima Beasiswa: Penelitian - Ria, Aurelia Rachel; Junias, Marylin Susanti; Takalapeta, Theodora (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine the relationship between social support and academic stress among scholarship recipients. The research employed a quantitative correlational approach with 165 respondents selected through purposive sampling. The instruments used were a social support scale based on Sarafino’s theory, which includes four dimensions, and an academic stress scale developed by Bedewy and Gabriel. Data analysis showed that all dimensions of social support were negatively correlated with academic stress. The results also indicated that emotional support and informational support were perceived as the most beneficial in helping students cope with academic pressure. However, the strength of the correlations ranged from weak to moderate, suggesting that academic stress is also influenced by other factors such as intrinsic motivation, emotion regulation, and time-management skills. These findings highlight the importance of social support as a protective factor, while also emphasizing that academic stress management interventions should include strengthening students’ internal factors as well as institutional support from the faculty.